Integration of Ethno-STEM-Based Sundanese Folklore E-Book in Science Learning for Elementary School Students' Character Development on Natural Event Materials - Dewiantika Azizah; Lucky Dewanti; Dede Latipah; Meitha Lesmiaty Khasyar; M. Arief Mardinansah; Dina Dina; Siti Nurpeti (Universitas Syiah Kuala, 2026)
The holiistiic iimplementatiion of sciience learniing based on hiigh order thiinkiing skiills (HOTS) iis a priimary need of the present era especiially on elementary school. However, are we aware that iin practiice, the cogniitiive aspect iis often priioriitiized at the expense of demonstratiing strong attiitudes, values, and sociial responsiibiiliity?. Thiis study proposes an enviironment-based learniing approach by analyziing the potentiial of a Sundanese folklore e-book based on the ethno-STEM (sciience, technology, engiineeriing, and mathematiics) approach to support contextual and holiistiic sciience learniing. A quantiitatiive approach was employed wiith pre-experiimental desiign of pretest-posttest control group desiign. The subject iin thiis study iis elementary school SDIiT Abaiis Bogor Ciity wiith 40 partiiciipant. Data analyze usiing paiired sampe t-test (iinterpretatiion control and experiiment class), n-gaiin (efect siize), and viisual liinear modelliing (male–female benefiiciiariies). The results iindiicate that the ethno-STEM e-book iintegratiion enhances the meaniingfulness of learniing by connectiing sciientiifiic concepts wiith local cultural contexts. Iintegratiion of ethno-STEM based Sundanese folklore e-books has the potentiial to be a promiisiing approach to sciience learniing iin synergiiziing sciience liiteracy, numeracy, and contextual character formatiion